Dual‐Functioning Molecular Carrier of Superoxide Radicals for Stable and Efficient Lithium–Oxygen Batteries. Issue 40 (22nd September 2020) - Bae, Youngjoon; Song, Hyelynn; Park, Hyeokjun; Lim, Hee‐Dae; Kwon, Hyuk Jae; Ko, Youngmin; Huynh, Chi; Ovalle‐Robles, Raquel; Kim, Yong Hyup; Im, Dongmin; Kang, Kisuk
Abstract: Low round‐trip efficiency and poor cycle stability remain the major challenges associated with lithium–oxygen (Li–O2 ) batteries. These issues are primarily triggered by or correlated to the radical species produced during the operation of Li–O2 cells, which lead to significant deterioration of the electrolytes and air electrodes. Regulation of the reactivity of these radical species would thus open up opportunities to suppress such side reactions. Herein, a dual‐functioning molecule that is capable of mitigating the reactivity of radical species produced in a Li–O2 cell by reversibly forming stable intermediate complex during both the discharge and charge processes is introduced. Specifically, 5, 5‐dimethyl‐1‐pyrroline N‐oxide (DMPO) is exploited, which has been widely used as a chemical agent to detect oxygen radicals, to induce the reversible formation of an intermediate complex, DMPO–O2 −, in the presence of superoxide radicals. It is demonstrated that DMPO mediates the O2 − ‐involved electrochemical reaction, leading to significant suppression of side reactions and a remarkably improved oxygen efficiency. Unexpectedly, it is also observed that upon charging, DMPO actively scavenges the superoxides from the surface of discharge products, thus substantially lowering the charging overpotential. The combined radical mediation and scavenging of superoxides result in cycle stability of a practical Li–O2 cell over 200 cycles with a specific capacity of 1000 mAh g −1 . The findings indicate the importance of controlling the reactivity of radical species and suggest a new pathway toward the realization of stable and efficient Li–O2 batteries. Abstract : A dual‐functioning molecular carrier of superoxide radicals is designed for the realization of Li–O2 batteries. It is demonstrated that the molecular carrier mediates the O2 − ‐involved electrochemical reaction, leading to suppression of side reactions and an improved oxygen efficiency. In addition, the molecular carrier actively scavenges the superoxides from the surface of discharge products, lowering the charging overpotential.